Covid-19 and thrombotic thrombocytopenic purpura: a case report - Mushtaq, Muhammad Zain; Mahmood, Saad Bin Zafar; Ali, Syed Ahsan; Shaikh, Muhammad Usman (Journal of the Pakistan Medical Association, 2023)
The clinical presentation of Covid-19 varies from being asymptomatic to developing acute respiratory distress syndrome and multi-organ dysfunction. The diffuse microvascular thrombi in multiple organs seen in the autopsy of Covid-19 patients are similar to that of thrombotic microangiopathy (TMA). TMA is characterised by thrombus formation in the microvasculature with laboratory findings of microangiopathic haemolytic anaemia (MAHA) and thrombocytopenia. A 49-year-old male presented to the Aga Khan University Hospital, Karachi. with fever, diarrhoea, altered level of consciousness, and a positive nasopharyngeal swab for SARS-CoV-2. He developed severe thrombocytopenia, MAHA with 5.8% schistocytes, and worsening renal function on the sixth day of admission. Diagnosis of thrombotic thrombocytopenic purpura (TTP) was established based on PLASMIC score, and he was successfully treated with intravenous (IV) Methylprednisolone, therapeutic plasma exchange and IV Rituximab. —Continue